Geomorphological mapping of the state of Paraná with digital classification method of landform patterns - Claudinei Taborda da Silveira; Ricardo Michael Pinheiro Silveira; Willian Bortolini; Victor Pierobom de Almeida (Revista Brasileira de Geomorfologia)
The digital classification method of landform patterns that was applied in the geomorphological mapping of the State of Paraná is presented. A Digital Terrain Model (MDT) was used to obtain three variables: 1) altimetric amplitude (AA), 2) average slope (AS) and 3) topographic position index (TPI), which were combined for classification compatible with the fourth geomorphological taxon, at a scale of 1:100,000. Sixteen classes of landform patterns were obtained: Flat Low Hills; Low Hills; Steep Low Hills; Terrain dissected between hills; Hills; High Hills; Dissected Hills; Steep High Hills; Elongated Structural Hills; Low Mountains; High Mountains; Plateau Edges; Strucutural Plateaus and Canyons; Fluviomarine Plain; Fluvial Plain and Colluvial Ramps. The method was consistent with the scale, the geomorphological characteristics and the intended representation and, after undergoing field verification with the collection of 225 points over 8,000km, it proved to be reliable at the desired level of representation, with overall mapping accuracy of 89.71%, with a slight predominance of overestimated areas (5.76%) compared to underestimated areas (4.53%), denoting the replicability of the method.